Penerapan Media Pembelajaran Fiqh Berbasis Google Sites dalam Meningkatkan Hasil Belajar Siswa Madrasah Diniyah Takmiliyah Ikromussalam - Siti Ruslina (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
Education plays a strategic role in instilling the values of morality, character, skills and as a means of knowledge transformation. The importance of the role of education for human beings coupled with the development of information and technology in the 21st century, has become a new challenge for education practitioners in developing creativity in utilizing technology in the process of learning and teaching activities. This research is a field research with a quantitative analysis approach to determine the influence of variable X (Google sites-based Fiqh learning media) on variable Y (student learning outcomes). The results of the study show that H0 is rejected and H1 is accepted with the interpretation that the application of Google Sites-based Fiqh learning media has a significant influence in improving student learning outcomes. This is due to learning media with audio-visual material treats and various practical activities of Fiqh material that can be manipulated through videos can help understanding and efficiency of time and environment. The improvement produced by the learning media can be categorized as "high".